Menakar Islam Wasathiyah Felix Siauw Dalam Akidah Islamiyah Melalui Dakwah Digitial Di Indonesia - Anwar, Zainul Anwar (Universitas Islam Negeri Raden Intan Lampung, 2024)
The digitalization of da'wah that is developing in Indonesia tends to trigger extreme thoughts in society which often lead to religious conflict and intolerance and radicalization. The focus of this research is to explain the Islamic concept of wasathiyah Felix Siauw with fanaticism in the elements of aqidah based on the Koran. As well as being an answer to community prbolematics related to the concept of Islamic wasathiyah adhering to the principles of aqidah, this research is intended to explore Felix Siauw's thoughts by using qualitative methods and library research (library research). and the Van Dijk approach to discourse analysis which focuses on the social dimension. the results of these findings state that wasathiyah Islam in the elements of aqidah can be applied to the community in strengthening the aqidah. And with the hope that the public understands what wasathiyah Islam is according to Felix Siauw's thoughts.